(untitled) (International Journal of Innovative Technologies in Economy, 2018)
The article seeks to investigate the problems of organizing accounting of receivables in the management of the enterprise, to take into account the updated requirements of normative legal acts on its implementation and to propose approaches to improvement. The study of legal requirements and the latest publications on the organization of accounts receivable in the management of the company involves only a partial display of the organization of accounts receivable, namely, either principles, or classification, the creation of a working plan of accounts, where the managerial component is not taken into account. The indicated shortcomings encourage the author to step-by-step proposals for the creation of an "Order on the policy of managerial accounting", which outlines the selected methodological principles of financial accounting of accounts receivable "Ordinance on the system of managerial accounting of enterprises" where it is necessary to specify developed regulatory acts, primary documents and registers of managerial accounting of receivables. The implementation of the proposal on the organization of management accounting of receivables into the practical activities of wholesale trade companies will allow this area to be divided into stages that facilitate tracking of the need to build or reduce its volumes, maturities, terms of calculation, additional work with counteragents, the need to apply to judicial authorities or enterprises outsource.